The Silk Road to Riches : How You Can Profit by Investing in Asia's Newfound Prosperity. - Mostrous, Yiannis G.; Gue, Elliott H.; Martchev, Ivan D. (FT Press Pearson Education [distributor], 2006)
Annotation